Current clinical concepts: Exercise and load management of adductor strains, adductor ruptures, and long-standing adductor-related groin pain - Thorborg, K. (Journal of Athletic Training, 2023)
Adductor-related groin pain is a common problem in sports. Evidence-based management of athletes with adductor strains, adductor ruptures, and long-standing adductor-related groin pain can be approached in a simple yet effective and individualized manner. In most cases, managing adductor-related pain in athletes should be based on specific exercises and loading strategies. In this article, I provide an overview of the different types of adductor injuries, from acute to overuse, including their underlying pathology, functional anatomy, diagnosis, prognosis, mechanisms, and risk factors. This information leads to optimal assessment and management of acute to long-standing adductor-related problems and includes primary, secondary, and tertiary prevention strategies that focus on exercise and load-based strategies. In addition, information on different options and contexts for exercise selection and execution for athletes, athletic trainers, and sports physical therapists in adductor injury rehabilitation is provided.